Implementation of virtual private network using point to point tunneling protocol mikrotik router at state fighter vocational school haurgeulis indramayu - Riana Febrianti; Sidik; Muhamad Ryansyah; Priatno (Institute of Computer Science (IOCS), 2022)
Using Point To Point Tunneling Protocol (PPTP) Mikrotik Router at SMK Pejuang Negeri Haurgeulis Indramayu Interconnection needs between networks will be needed, especially in an agency that has many branch offices. To facilitate access to communication and data retrieval between offices, a Virtual Private Network (VPN) network is needed. Virtual Private Network (VPN) is a communication technology that allows local networks to be connected to each other via public networks. Data security and data transmission closure from unauthorized access in its transmission on the internet are the main standards in VPNs, so that VPNs always include the main features, namely encryption and tunneling.